Detection of the posterior superior alveolar artery in the lateral sinus wall using computed tomography/cone beam computed tomography: a prevalence meta-analysis study and systematic review. Issue 11 (November 2015) - Varela-Centelles, P.; Loira-Gago, M.; Seoane-Romero, J.M.; Takkouche, B.; Monteiro, L.; Seoane, J.
Abstract A systematic search of MEDLINE, Embase, and Proceedings Web of Science was undertaken to assess the prevalence of the posterior superior alveolar artery (PSAA) in the lateral sinus wall in sinus lift patients, as identified using computed tomography (CT)/cone beam computed tomography (CBCT). For inclusion, the article had to report PSAA detection in the bony wall using CT and/or CBCT in patients with subsinus edentulism. Studies on post-mortem findings, mixed samples (living and cadaveric), those presenting pooled results only, or studies performed for a sinus pathology were excluded. Heterogeneity was checked using an adapted version of the DerSimonian and Laird Q test, and quantified by calculating the proportion of the total variance due to between-study variance (Ri statistic). Eight hundred and eleven single papers were reviewed and filtered according to the inclusion/exclusion criteria. Ten studies were selected (1647 patients and 2740 maxillary sinuses (study unit)). The pooled prevalence of PSAA was 62.02 (95% confidence interval (CI) 46.33–77.71). CBCT studies detected PSAA more frequently (78.12, 95% CI 61.25–94.98) than CT studies (51.19, 95% CI 42.33–60.05). Conventional CT revealed thicker arteries than CBCT. It is concluded that PSAA detection is more frequent when CBCT explorations are used. Additional comparative studies controlling for potential confounding factors are needed to ascertain the actual diagnostic value of radiographic explorations for assessing the PSAA prior to sinus floor elevation procedures.